The impact of low birthweight in infant patterns of regulatory behavior, mother-infant quality of interaction, and attachment. (September 2022) - Fuertes, Marina; Antunes, Sandra; Martelo, Inês; Dionisio, Francisco
Abstract: It remains unclear whether infants born preterm are more likely to develop an insecure attachment with their mothers. In this study, instead of using gestational age criteria, we observe attachment in infants born with very low birthweight. Although the collinearity between gestational age and birthweight is high, infants born with very low birthweight for their gestational age tend to stay more days in NICU and to have more comorbidities than other infants with the same gestational age. Thus, we wonder about the impact of low gestational birth (per se) in infants' regulatory behavior, the quality of mother-infant interactions, and attachment security. The participants are 71 infants' weight lower than 1599 g of gestational weight (varying between 23 and 34 weeks of gestational) and their mothers. Dyads were observed in free play and during Face to Face Still-Face paradigm with infants at 3 months of corrected age. At 12 months of corrected age, mother-infant attachment was observed during Strange Situation. Results indicate that infants with low/very low gestational birthweight have high levels of insecure attachment (70 %) and non-positive patterns of regulatory behavior (64 %). Maternal and infant interactive behavior is highly associated with infant attachment. In turn, maternal interactive behavior is associated with gestational age, birthweight, and number of days in NICU. Highlights: Infants born with very low birthweight and at a family and social disadvantage are at risk for attachment insecurity Infant regulatory behavior and mother-infant interactive behavior impact infant attachment quality Maternal sensitivity is affected by prematurity related factors as gestational age, birthweight, and number of days in NICU Insecure-ambivalent infants are more likeky to uptake antibiotics in the first year of life than other infants